Analysis of the Effect of Good Corporate Governance, Leverage and Financial Performance on Profit Management - Ermalina; Berlianingsih Kusumawati; Siti Maryama; Sulistyo Seti Utami; Iwan Subandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The company definitely strives to display the best possible financial statements. Financial statements are often used as a reference to determine the status of a company. In order to display good financial statements, it is not uncommon for company managers to decide to do profit management. Profit management is basically seen as unethical, but there are quite a few other perspectives that show that profit management is not a bad thing. There are several factors that can affect profit management. Factors that can affect profit management are good corporate governance, leverage, and the company's financial performance. This study aims to analyze the relationship of these three variables to profit management. The method used is a quantitative method. The data used is secondary data. Data analysis was performed using multiple linear regression. The results showed that good corporate governance has a negative and significant influence on profit management, leverage has no influence on profit management, and financial performance has a negative influence on profit management